“Transferring the practice of performance appraisal in Chinese MNCs subsidiaries in the UK” - Rondoni, Agnese (2017)
Within the context of globalisation, an increasing interest lies on the analysis of the transferability of human resource (HR) practices between different countries, as a source to gain competitive advantage. So far, the bulk of the existing literature is concerning with the transferability of HR systems from developed to developing countries. What emerged was that practices have different degree of adaptability and this is due to host countries’ culture and habits, which sometimes might limit and even act as a constraint to the introduction of Western managerial knowledge overseas, as the literature revealed about the implementation of the practice of Performance Appraisal (PA) in China. On the contrary, little is known about how MNCs from developing countries operate in more advanced markets in the transfer of their HR systems. The first aim of this study was to try to fill this gap by analysing whether cultural and other limitations, as the lack of Chinese managers’ competences, affect Chinese MNCs also when implementing the practice of PA in the UK. China is a valuable sample both because of its rooted cultural tradition and its increasing value in Outward Foreign Direct Investment (OFDI) of which Europe is now source for around 6%. The research also sought to investigate the strategy behind the transfer of the system of PA between headquarters and subsidiaries. In their process of internationalisation Emerging Markets MNCs are normally assumed to operate in two ways: on the one hand, they work as “knowledge seekers”, which means that they tend to acquire Western advanced managerial practices and transfer them back to their respective headquarters, through a process known as “reverse diffusion”. On the other, they use an exportive approach which relies on their ability to autonomously operate in the advanced economies and implement their preferred HR practices directly from their headquarters. Drawing on a study of the implementation of the system of PA in Chinese MNCs operating in the UK, the present study shows a twofold result. On one side, it reveals that cultural differences and lack of managerial skills do not exercise any influence on the transferability of the practice in the context of a developed country. On the other, it also reveals that a practice of exportive approach was implemented by almost all the organisations for the transfer of the practice between headquarters and UK subsidiaries.